Relativistic velocity addition and calculi based on hyperbolic tangent - Bashirov, Agamirza E.; Genc, Sinem (Nova Science Publishers, Inc., 2020)
where c is the speed of the light. This is a special case when the velocities v1 and v2 have the same direction. In more general case, when v1 and v2 have different directions, the formula is more complicated and does not have ordinary properties such as linearity, commutativity, associativity, etc. In this work, we are aimed to develop two calculi over the specific algebraic operations, preserving the preceding relativistic addition formula and having all ordinary properties. © 2020 by Nova Science Publishers, Inc. All rights reserved.